Respect and Protection of Human Dignity in Human Rights Law in Emergency Situations in International Law and its Relation to Customary Values in Indonesia - Irman Putra; Arief Fahmi Lubis (Budapest International Research and Critics University, 2022)
In the context of an emergency situation such as a social conflict or war, such respect and protection must also be extended to those who are on the opposite side of us. The concept of respecting and protecting human dignity is an idea that has existed for a long time and has become an integral part of human civilization to show that the concept of respecting and protecting human dignity is universal. local customs and wisdom. This research problemon how the development of respect and protection of human dignity in emergency situations in international law and how the efforts of the International Committee of the Red Cross (ICRC) in seeking international law affinity in the above context with customary values. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study indicate thatFirst, Over time, the concept of respecting and protecting human dignity has also become an inseparable part of international law, Second, that the concept of respecting and protecting human dignity is an idea that has existed for a long time and has become an integral part of human civilization, Third, each regulation, which is developed in a simple manner, will be complemented by relevant religious customs and norms that are present in various forms in Indonesia where there is a wealth of relevant local traditions, known as adat originating from a rich cultural heritage and diverse influences.